Mongolia : Staff Report for the Third Review Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Mongolia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
This IMF Staff Report discusses Mongolia's Third Review Under the Extended Fund Facility. Mongolia's performance under the program thus far has been strong. The economy is recovering better than expected, with real GDP growth of 5.1 percent in 2017. The combination of strong policy implementation and a supportive external environment has helped the authorities over-perform on all end-December 2017 quantitative targets. However, the performance on structural reforms has been mixed with some delays on structural benchmarks under the program and reversals of three fiscal measures considered during previous reviews. Given the strong performance to date, continued improvement in the macro outlook, and still high public debt, the authorities committed to tightening the fiscal and reserve targets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet